Genetic polymorphisms of the drug-metabolizing enzyme CYP2C19 in the Uyghur population in northwest China. (2nd July 2016) - Jin, Tianbo; Zhang, Mingxia; Yang, Hua; Geng, Tingting; Zhang, Ning; Feng, Tian; Ma, Yajuan; Yuan, Dongya; Kang, Longli
Abstract: 1. CYP2C19 is a clinically important enzyme and is involved in the metabolism of approximately 10% of drugs used in daily clinical practice. Previous studies mainly focused on Chinese Han populations or other ethnic groups, little is known about Uyghur populations. 2. The present study was designed to determine the genetic basis of CYP2C19 polymorphisms. 3. We used direct sequencing to investigate the promoter, exons and surrounding introns, and 3′-untranslated region of the CYP2C19 gene in 96 unrelated healthy Uyghur individuals. 4. A total of 31 different CYP2C19 polymorphisms were identified in the Uyghur population, three of which were novel, including two nonsynonymous variants (57807A > M, Gln279Pro and 19257G > R, Asp262Asn) and one synonymous variants in exon 5 (19184T > Y, Leu237Leu). In addition, CYP2C19 *1, *2 and *3 alleles showed frequencies of 83.34%, 14.06% and 2.08%, respectively. 5. This is the first study that systematically screened the polymorphisms of the whole CYP2C19 gene in Uyghur population. Hence, our results provided important information on CYP2C19 polymorphisms in Uyghur population and could be helpful for future personalized medicine studies in Uyghur population generally.